DRIVING ICT ADOPTION AMONG REAL ESTATE AGENTS: AN EXTENDED TECHNOLOGY ACCEPTANCE MODEL - Mohamad, Murni; Mohd Aini, Ainoriza; Alias, Anuar (International Journal of Property Sciences (E-ISSN: 2229-8568), 2024)
TThe practice of real estate agents and the extent to which Information and Communication Technology (ICT) is applied in Malaysia appears to be more specialised and diverse with the exploration of technology and innovation. Due to the increasing interest in using more innovative marketing and negotiation techniques, this study focuses on real estate agents' acceptance as well as the intention to use ICT in Malaysia according to the extended Technology Acceptance Model (TAM). In this study, a sample including 400 real estate agency practitioners was surveyed and analysed using Partial Least Squares-Structural Equation Modelling (PLS-SEM). The findings show that Perceived Usefulness (PU), Perceived Ease of Use (PEOU), as well as Trust (TRU) affect Behavioural Intention (BI). On the other hand, PU is affected by PEOU as well as Service Quality (SERQ). Meanwhile, PEOU is affected by Perceived Enjoyment (ENJ) as well as Innovativeness (INNO). These results indicate that ICT acceptance among real estate agents can be improved by providing them with high-quality service, fostering perceived enjoyment, building trust, and establishing innovative ICT solutions tailored to real estate agents' needs.